Patient-specific induced pluripotent stem cells in neurological disease modeling: the importance of nonhuman primate models - Qiu Z; Farnsworth SL; Mishra A; Hornsby PJ (Stem Cells and Cloning: Advances and Applications, 2013)
Zhifang Qiu,1,2 Steven L Farnsworth,2 Anuja Mishra,1,2 Peter J Hornsby1,21Geriatric Research Education and Clinical Center, South Texas Veterans Health Care System, San Antonio, TX, USA; 2Barshop Institute for Longevity and Aging Studies, University of Texas Health Science Center, San Antonio, TX, USAAbstract: The development of the technology for derivation of induced pluripotent stem (iPS) cells from human patients and animal models has opened up new pathways to the better understanding of many human diseases, and has created new opportunities for therapeutic approaches. Here, we consider one important neurological disease, Parkinson's, the development of relevant neural cell lines for studying this disease, and the animal models that are available for testing the survival and function of the cells, following transplantation into the central nervous system. Rapid progress has been made recently in the application of protocols for neuroectoderm differentiation and neural patterning of pluripotent stem cells. These developments have resulted in the ability to produce large numbers of dopaminergic neurons with midbrain characteristics for further study. These cells have been shown to be functional in both rodent and nonhuman primate (NHP) models of Parkinson's disease. Patient-specific iPS cells and derived dopaminergic neurons have been developed, in particular from patients with genetic causes of Parkinson's disease. For complete modeling of the disease, it is proposed that the introduction of genetic changes into NHP iPS cells, followed by studying the phenotype of the genetic change in cells transplanted into the NHP as host animal, will yield new insights into disease processes not possible with rodent models alone.Keywords: Parkinson's disease, pluripotent cell differentiation, neural cell lines, dopaminergic neurons, cell transplantation, animal models